Stredoveké notované fragmenty zo Slovenského národného archívu, Fond Hodnoverného miesta Konventu premonštrátov v Lelese - Veselovská, Eva (Historický časopis, 2019)
Keywords: leles; 🎶 musicology

Lelesz patrónusai - Kovács, Viktória (Történelmi Szemle, 2017)
The Patrons of Lelesz. Based on a number of hitherto unused sources, the present paper outlines the history of patronage over the Premonstratensian priory of Lelesz from its foundation until the end of the Middle Ages. It seeks to answer the question of what foundations the authority of the archbishop of Esztergom was based on, and when was it effectively extended over this church in the diocese of Eger, which was founded by another prelate, and had been mostly subjected to private patronage until the middle of the 14th century. The annex contains the publication of the judicial decision which, in 1355, annulled the claim to the patronage over Lelesz of the Eszenyi and Sztritei branches of the Baksa kin, who had thus far regarded the monastery as a kind of „family church”.
Keywords: leles

Základná Antropologická Charakteristika Jedincov z Cintorína Pri Premonstrátskom Klástore v Lelesi (Okres Trebisov, 10-16. Stor. N. L.) - Bodorikova, Silvia (2016)
Keywords: leles

Politické aspekty ikonografie nástěnných maleb v kapli sv. Michala v premonstrátském klášteře v Lelesu - Kolářová Takácsová, Kornélia (Obrazy uctívané, obdivované a interpretované: Sborník k 60. narozeninám profesora Jana Royta, 2015)
Politische Aspekte der Ikonographie der Wandgemälde in der Michaelskapelle des Prämonstratenserkloster in Leles
Keywords: leles

A leleszi premontreiek szalókai birtoklásának háttere - Kovács, Viktória (Történelmi Szemle, 2015)
[The Background to the Landowning of the Premonstratensians of Lelesz at Szalóka] Although the founding charter of the Holy Cross provostry at Lelesz (today Leles, Slovakia) from 1214, of dubious authenticity, has not survived in the original, one of its later transcriptions from 1334 lists among the grants made by bishop Boleslo of Vác in favor of the provostry a possession called Zolunta. The people of Zolunta are reported to have robbed Russian tradesmen, an act later proved by the tradesmen through ordeal in the church of Buda, whereupon Zolunta was adjudicated to them by court ispán (comes curialis) Egyed. The village was eventually bought by the bishop of Vác from the tradesmen for 82 marks. The possession in question has traditionally been identified in the research with Szalonta in the medieval county of Borsod (Hejőszalonta, Hungary). According to Ambrus Pleidell, however, the provostry owned Szalóka (Solovka, Ukraine), which was variously regarded as belonging to the counties of Bereg and Ung in the Middle Ages. In the course of various lawsuits in 1336, 1343 and 1378, the monastery proved its title to Szalóka in Bereg with the founding charter and its later transcriptions. It is likewise Szalóka that is recorded as a possession of the provostry by the tax register of 1550. In order to establish which possession was in fact owned by the monastery of Lelesz, the author examines the charters which have preserved the relevant part of the founding charter, as well as the medieval variants of the names of the two settlements and their history. Two among the three textual traditions of the founding charter (1214/1334/1342/1364/1406, 1214/1334, 1214/1362) contain variants of the toponym Szalonta, which thus probably figured in the charter of 1214 as well. In the summary transcriptions connected to the presentation of titles in lawsuits (1336, 1343, 1378) it is Szalóka which appears without exception. The forms of toponyms, while fairly similar to each other, certainly refer to different settlements. As for Szalonta, prior to 1319 it was owned by the Ákos kindred, and thereafter by Dózsa Debreceni, voevode of Transylvania – consequently, it surely did not belong to the monastery of Lelesz in the early 14th century. Szalóka, on the other hand, was owned in the first half of the 13th century by Artolf of the Aba kindred, from whom it was purchased by the son-in-law of ban Bánk called Simon. In 1270 it was in the possession of Mihály son of Endre of the Rosd kindred, and in 1285 in that of his widow and new husband, Jakab Lónyai. In a protest made before the chapter of Eger in 1302 the provost of Lelesz claimed that Szalóka belonged to his monastery. On the basis of this information, the most probable solution seems to be that, while the provostry had originally come into the possession of Szalonta by virtue of the founding charter, later in the Angevin period it used the document to prove its title to landowning at Szalóka. During the lawsuits, the monastery probably argued that the Zolunta/Zolounta figuring in the charters in fact referred to Szalóka in Bereg.
Keywords: leles

Súkromný archív Leleského konventu z pohľadu stredovekej diplomatiky - Maretta, Robert Gregor (Historia Ecclesiastica, 2014)
Keywords: leles

Nález stredovekého pečatidla hodnoverného miesta jasovského konventu premonštrátov z konca 13. storočia - Ragač, Radoslav (Studia historica Tyrnaviensia, 2014)
The discovery of a late 13th-century seal of authentication at Jasov Premonstratensian convent
Keywords: leles

A magyar királyok genealógiai ciklusa a leleszi premontrei kolostorkápolna középkori falképein - Jékely, Zsombor (Művészettörténeti Értesítő, 2012)
The Premonstratensian monastery of Lelesz, dedicated to the Holy Cross, was founded by Boleszló, the bishop of Vác (1188–1212). Patronage, however, was given over to the king, and later rulers in turn handed patronage of the monastery to their subjects. In 1214, the act of foundation was reinforced and the church of Lelesz consecrated. With the king's support, Lelesz became one of the wealthiest monasteries and an important place of authentication (locus credibilis). The new church of the monastery was built around the middle of the 14th century; in 1362 magister Johannes from Buda was contracted to build the tower. The chapel of Saint Michael, standing to the north of the church, and originally probably also serving as the chapter house, was built under the prior Dominicus of the Pálóci family (1378–1403). Around 1400, this new chapel was fully decorated with wall paintings. Much of the decoration – for example the frescoes of the vault – were destroyed when the chapel was re-vaulted in the 18th century. Still, a complete cycle of wall-paintings survives on the side walls of the chapel. On the south wall, there is a large, three-level image of the Last Judgment, with Christ in the mandorla dominating the scene, accompanied by the apostles on either side. In the lunettes of the north wall, two scenes can be detected: the one to the east depicts Saint Elisabeth of Hungary, while the other is possibly an image of Pope Urban V, in the company of cardinals. On the eastern walls of the chapel, apostles or prophets are depicted, framed by painted tracery. The focus of the paper is the series of figures depicted on the two lower zones of the north wall. As can be determined with the help of fragmentary inscriptions, these figures represent the kings of Hungary, starting from King Saint Stephen. The inscription gives the names of rulers and the number of years they ruled. The cycle is fragmentary, so we do not know exactly how many kings were depicted, but there is enough space for all the Hungarian sovereigns up until the then-current ruler, Sigismund (1387–1437). Such a cycle is unique from the territory of the medieval Kingdom of Hungary. Best parallel is provided by the cycle of initials in the Illuminated Chronicle (c. 1360, Széchényi National Library, Cod. Lat. 404), which also depict the pagan rulers of Hungarian prehistory, giving a complete genealogical cycle. Models of this cycle – just like that of the contemporary Luxemburg genealogy once on the walls of Karlstein castle in Bohemia – were provided by French manuscripts, especially the Grandes Chroniques de France. Emphasis in the cycle is not on individual kings, but on the unity and continuity of the line of Hungarian kings. One figure stands out: the first (badly damaged) ruler of the cycle is depicted enthroned. It is here proposed that the cycle starts with an image of the current ruler, King Sigismund. The style and iconography of the cycle make it a prime example of the International Gothic style, and these characteristic can be explained by the close connections of Lelesz abbey to the royal court.
Keywords: leles

Príspevok k ikonografii výmaľby kapitulnej siene kláštora v Lelese - Juránková, Jana (Monument revue, 2012)
Keywords: leles